Caracterización de POPs y PAHs en fragmentos plásticos: Estudio de Caso en el Callao - Herrera Amezquita, Oscar (2024)
This study evaluates microplastic pollution, persistent organic pollutants (POPs), and polycyclic aromatic hydrocarbons (PAHs) in the Bay of Callao, Peru. Sampling was conducted at six stations from Playa Pachacútec to La Punta, 500 meters from the coast. The collected microplastics were quantified, identifying adsorbed contaminant groups: PAHs, polychlorinated biphenyls (PCBs), DDT metabolites (DDX), pentachlorobenzene (PeCB), hexachlorobenzene (HeCB), and hexachlorocyclohexane (HCHs). The results showed 97.1204 items/m³ of microplastics, equivalent to 5,170,073.7321 items/km². Concentrations were 1749 ng/g for PAHs, 151.7 ng/g for PCBs, 311 ng/g for DDX, 13.0 ng/g for PeCB and HeCB, and 3.72 ng/g for HCHs. Compared to other studies, the Bay of Callao presents similar or higher contamination levels, especially in PAHs and DDX. This underscores the need for mitigation measures to reduce marine pollution and protect human health.